Evidence found : an approach to crime scene investigation - Miranda, David (Academic Press, an imprint of Elsevier, 2015)
Evidence Found: An Approach to Crime Scene Investigation examines the thought processes that can lead to forensic errors. It includes tips and tricks gleaned from the author's 25 years of relevant experience in the field. As both low and high profile crime scene investigations suffer from errors that lead to negative impacts on both investigation results and court proceedings, this text evaluates the decision-making process, including case studies and logical arguments that provide a framework readers can use to recognize, evaluate, and alter negative decision-making patterns, including self-examination, before they negatively impact an investigation or the overall operation of a forensic unit.